Membangun Spirit Belajar dalam Perspektif Burhanuddin Az-Zarnuzi - Lubis, Lismaya; Junaidi Arsyad (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This article aims to examine the concept of building a spirit of learning based on the views of Burhanuddin Az-Zarnuzi, a leading scholar in the 13th century. He underlines the importance of an educational environment that facilitates student engagement and activity. Burhanuddin Az-Zarnuzi also emphasizes the importance of applying a holistic approach to learning that considers in a balanced manner the intellectual, emotional, and spiritual aspects of each student. By collecting data from various primary and secondary sources related to Burhanuddin Az-Zarnuzi's thoughts, this research uses a descriptive-analytical method. The results of the analysis show that Burhanuddin Az-Zarnuzi's perspective and contribution in building the spirit of learning can be useful for teachers and people who want to improve their learning spirit. In conclusion, this study emphasizes how important it is to build a strong spirit of learning in schools. Burhanuddin Az-Zarnuzi's holistic approach and perspective on intrinsic motivation can serve as a basis for building effective learning strategies. It is hoped that by understanding and applying these principles, people can achieve their learning potential optimally and develop themselves thoroughly.